Advancing Digital Extension Education: Development and Validation of Digital Learning Engagement Scale - Pakala, Yamini; Guniganti, Sunitha (Indian Journal of Extension Education, 2025)
Digital transformation has revolutionized extension education and professional upskilling, revealing significant gaps in learning engagement assessment within digital contexts. Conventional classroom-based scales fail to capture multifaceted digital engagement in AI-augmented, asynchronous environments, overlooking self-regulation difficulties, learner isolation, and adaptive interactions. This hampers organizations and extension practitioners from identifying disengagement early and designing evidence-based interventions. Addressing this, an 18-item Digital Learning Engagement Scale (DLES) was developed through robust psychometric evaluation, content validation by eight experts. Data was collected from 461 digital learning platform users. Exploratory factor analysis (n=227) using principal axis factoring is chosen to handle correlated engagement dimensions, identified a stable four-factor structure (behavioural, emotional, cognitive and psychological engagement)explaining 66.93 percent of variance (KMO=0.937, Bartlett’s p < 0.001). Confirmatory factor analysis confirmed excellent model fit (χ²//df = 1.34, CFI = 0.945, TLI = 0.935, RMSEA = 0.065, SRMR = 0.057) with strong internal consistency (α = 0.86 -0.91), composite reliability (CR = 0.87- 0.91), convergent and discriminant validity. The DLES enables extension professionals, educators, and organizations to assess engagement, identify barriers, and implement targeted data-driven interventions, improving retention and learning effectiveness.